The development of a remuneration system for the oil and gas sector (Journal of Economic Research & Business Administration, 2017)
Today, the grading system is the best and the only justifiable systemof calculating salaries, which allows to clean with basic pay. That is, thegrading system allows you to “align” wages and the business logic, anduntie the knot of problems related to motivation of the staff of the oil andgas sector. Grading is regarded as a technology to attract and retain highlyqualified personnel in the industry. Presents the main stages of building ofthe process of grading. Shows the main benefits and risks of the remunerationsystem on the basis of grading. Focused on the fact that the processof grading does not end at the stage of development and implementation.In the subsequent years of system operation is necessary to continuouslyundertake measures for its control, correction and verification of the adequacyalong with the changing conditions of the labour market. Developmentof grades requires a lot of time and material investments, but withthe right approach, the organization obtains a tool that unites all the mainsystems of personnel management – remuneration, motivation, evaluationand training. The article presents in summary form the recommendationsof practitioners the introduction of grading in the organization of the oiland gas sector.